1985
DOI: 10.1093/ajcn/42.5.788
|View full text |Cite
|
Sign up to set email alerts
|

Cereal dietary fiber consumption and diverticular disease: a lifespan study in rats

Abstract: The relationship between consumption of dietary fiber (DF) from white bread, wholemeal bread, or bran and the development of diverticular disease of the colon has been investigated in a lifespan study using 1800 Wistar rats in nine diet groups. Use of the rat as a model for the human condition was validated by demonstration of significant relationships between fiber intake and fecal output and transit time, and the observation of true acquired diverticula, both single and multiple. Significant inverse relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 25 publications
0
25
0
6
Order By: Relevance
“…Typically these diets were high in animal protein or fat and very low in fiber [70,71] . Increasing the fiber content of these basal diets reduced the DD incidence [72] . Indirectly, these rat models suggest a role for the intestinal flora in DD; Carlson and Hoezel [71] found that they were able to induce DD in rats fed Karaya gum as dietary fiber source, but not in rats where Psyllium seed husks or semi-fibrous cellulose flour was the dietary fiber source.…”
Section: Bread and Cereal Productsmentioning
confidence: 97%
“…Typically these diets were high in animal protein or fat and very low in fiber [70,71] . Increasing the fiber content of these basal diets reduced the DD incidence [72] . Indirectly, these rat models suggest a role for the intestinal flora in DD; Carlson and Hoezel [71] found that they were able to induce DD in rats fed Karaya gum as dietary fiber source, but not in rats where Psyllium seed husks or semi-fibrous cellulose flour was the dietary fiber source.…”
Section: Bread and Cereal Productsmentioning
confidence: 97%
“…Evidence from epidemiological studies suggests that breast cancer risk also may be lowered by an increased dietary fiber consumption (Rose, 1990). There are several studies that have addressed this important question using controlled experimental animal models (Fisher et al, 1985;Cohen et al, 1991;Arts et al, 1991), but the overall results have been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…During the same year, Arts et al (1991) reported that high levels of dietary fiber (wheat bran) fed to female F344 rats commencing 3 weeks before MNU treatment and for the duration of the study resulted in a significant reduction ( p Ͻ 0.01) in mean mammary carcinoma weight; however, the percent of rats with mammary carcinomas, the mean number of mammary carcinomas per rat and the mean latency period of mammary carcinoma appearance were not influenced significantly by the high-fiber diet. Similarly, Fisher et al (1985) reported the lack of a significant effect of high levels of dietary fiber (white bread, wholemeal bread or bran) on the spontaneous development of mammary fibroadenomas or mammary carcinomas in female Wistar rats fed the fiber-supplemented diets throughout their life-span. From these reports, it is reasonable to conclude that a suppressive role for dietary fiber in the development and/or growth of mammary gland tumors in experimental animals has not been established.…”
mentioning
confidence: 94%
“…Nonetheless, corroborative animal data does exist. Most notable is a study of rats fed diets of varying fiber content throughout their natural lifespan; 45% of the rats on the lowest fiber diet developed diverticula, compared with only 9% of those fed the highest fiber diet (16).…”
Section: Etiology/pathogenesismentioning
confidence: 99%